1967
DOI: 10.1136/thx.22.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Early jaundice after open-heart surgery

Abstract: Two hundred and thirty-two patients subjected to open-heart surgery have been analysed regarding early post-operative jaundice. The overall incidence of jaundice was 13%, being 55% where the mitral valve and 5% where the aortic valve was predominantly involved. Only one out of 59 patients in whom a congenital lesion was repaired became jaundiced. Hyperbilirubinaemia without jaundice was common. The biochemical pattern of the jaundice was singularly constant, the most striking feature being the rise in serum bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
1

Year Published

1970
1970
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
4
42
1
Order By: Relevance
“…The decreased hepatic capacities for bilirubin disposal and bile transport, in addition to the haemolysis from CPB, cardiotomy suction, and mechanical prosthesis result in the postoperative hyperbilirubinemia. Both Weber [1] and Lockey [2] proposed that haemolysis contributed to postoperative jaundice; in contrast, Collins [3] and Chu [4] reported that serum TB concentration mainly resulted from increased CB, i.e., hepatic cellular jaundice. However, for the patients with postoperative hyperbilirubinemia in our study, 80.2% of the increased TB was due to an increase of both CB and UCB; 56.2% reached peak TB concentration on the first postoperative day, 33.5% on the second day and 10.3% on the seventh day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The decreased hepatic capacities for bilirubin disposal and bile transport, in addition to the haemolysis from CPB, cardiotomy suction, and mechanical prosthesis result in the postoperative hyperbilirubinemia. Both Weber [1] and Lockey [2] proposed that haemolysis contributed to postoperative jaundice; in contrast, Collins [3] and Chu [4] reported that serum TB concentration mainly resulted from increased CB, i.e., hepatic cellular jaundice. However, for the patients with postoperative hyperbilirubinemia in our study, 80.2% of the increased TB was due to an increase of both CB and UCB; 56.2% reached peak TB concentration on the first postoperative day, 33.5% on the second day and 10.3% on the seventh day.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in techniques of perioperative management in cardiac operations, CPB, and cardiac anaesthesia, early hyperbilirubinemia after modern extracorporeal circulation surgery still occurs frequently. With regard to the effects of the disease and operation category, controversies exist about whether incidence differs among different disease category [2,3] . The current results showed that postoperative hyperbilirubinemia occurred more frequently in patients receiving valvular replacements than in patients undergoing CABG or operation for CHD (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 In one retrospective study early jaundice was seen in 13% of 232 patients undergoing open heart operations. 4 In a similar study 8.6% of 736 patients undergoing open heart surgery developed postoperative jaundice.5 There have, however, been only a few prospective inquiries into the incidence and causes of postoperative jaundice. The prospective study of Evans et a16 revealed a much higher incidence (21%) of postoperative jaundice in patients having major noncardiac operations.…”
mentioning
confidence: 99%